Developing the Oral Skill in Online English Courses Framed by the Community of Inquiry - Luz Edith Herrera Díaz; Darlene González Miy (Universidad Nacional de Colombia, 2017)
Over the last decade, the community of inquiry framework has proved successful for online learning experiences in diverse disciplines, although studies in the teaching of English as a foreign language arena are still scarce. In this vein, this article reports a preliminary study about the development of the oral skill in a Basic English online course, uncovering the relationship between the community of inquiry framework (with its three forms of presence: teaching, cognitive, and social) and some indicators of the oral skill. Findings, based on learners' perceptions, confirmed the existence of such framework and suggest that the teaching presence fosters grammar, accuracy, and vocabulary. Discussion of findings, limitations of the study and future possible research actions conclude this report.